2012
DOI: 10.1371/journal.pone.0044740
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Signalling Is Activated in the Postischemic Heart and May Influence Remodelling

Abstract: BackgroundAll-trans retinoic acid (atRA), an active derivative of vitamin A, regulates cell differentiation, proliferation and cardiac morphogenesis via transcriptional activation of retinoic acid receptors (RARs) acting on retinoic acid response elements (RARE).We hypothesized that the retinoic acid (RA) signalling pathway is activated in myocardial ischemia and postischemic remodelling.Methods and FindingsMyocardial infarction was induced through ligating the left coronary artery in mice. In vivo cardiac act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…ATRA signaling has been reported by Bilbija et al (5) to be activated in the mouse heart after permanent coronary artery ligation. These investigators further proposed that ATRA signaling may play a role in regulating damage and repair during heart remodeling (5).…”
Section: Levels In Bco1mentioning
confidence: 85%
“…ATRA signaling has been reported by Bilbija et al (5) to be activated in the mouse heart after permanent coronary artery ligation. These investigators further proposed that ATRA signaling may play a role in regulating damage and repair during heart remodeling (5).…”
Section: Levels In Bco1mentioning
confidence: 85%
“…Furthermore, the effect of PX-478 is limited to hypoxia, as angiogenic signaling is not altered in the presence of PX-478 under normoxic conditions (28). PX-478 does not appear to alter retinoic acid signaling, a pathway previously shown to affect HO formation (32). Separately, we used rapamycin, which inhibits Hif1α through the mammalian target of rapamycin (mTOR) (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…The treatments with RA or SB, alone or in combination prevented the expression of MMPs and activated the expression of TIMPs in heart tissue of Npr1 ϩ/Ϫ mice. Moreover, in vivo studies have shown that RA not only prevents ventricular fibrosis and remodeling during the development of hypertension but also activates RA signaling after myocardial infarction (4,37). Those previous findings support our hypothesis regarding the protective mechanisms of RA and SB in 1-copy haplotype Npr1 mice.…”
Section: Discussionmentioning
confidence: 99%